Pathophysiological and cognitive mechanisms of fatigue in multiple sclerosis. Issue 6 (25th January 2019) - Manjaly, Zina-Mary; Harrison, Neil A; Critchley, Hugo D; Do, Cao Tri; Stefanics, Gabor; Wenderoth, Nicole; Lutterotti, Andreas; Müller, Alfred; Stephan, Klaas Enno
Abstract : Fatigue is one of the most common symptoms in multiple sclerosis (MS), with a major impact on patients' quality of life. Currently, treatment proceeds by trial and error with limited success, probably due to the presence of multiple different underlying mechanisms. Recent neuroscientific advances offer the potential to develop tools for differentiating these mechanisms in individual patients and ultimately provide a principled basis for treatment selection. However, development of these tools for differential diagnosis will require guidance by pathophysiological and cognitive theories that propose mechanisms which can be assessed in individual patients. This article provides an overview of contemporary pathophysiological theories of fatigue in MS and discusses how the mechanisms they propose may become measurable with emerging technologies and thus lay a foundation for future personalised treatments.